A method for preparing a high-performance polymer / inorganic ceramic composite solid electrolyte

By covering the polydopamine layer on the surface of the inorganic ceramic and combining polymer and inorganic ceramic composite technology, a high-performance solid electrolyte membrane was prepared, which solved the problems of low mechanical strength and interface incompatibility, and significantly improved the electrochemical performance and thermal stability of lithium metal batteries.

CN114927749BActive Publication Date: 2025-02-28HARBIN UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210386123.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-13
Publication Date
2025-02-28
Estimated Expiration
2042-04-13

AI Technical Summary

Technical Problem

The existing pure inorganic solid electrolyte has low mechanical strength, interface problems with the electrode material, and low ion conductivity and ion migration number at room temperature.

Method used

Using a polymer/inorganic ceramic composite solid electrolyte preparation method, a composite electrolyte membrane consisting of polydopamine (PDA) on the surface of Li6.4La3Zr1.4Ta0.6O12 (LLZTO) was coated with a polydopamine (PDA) layer, and a solution casting method was used to design a composite electrolyte membrane composed of polyacrylonitrile (PAN), (polyvinylidene fluoride-hexafluoropropylene) copolymer (PVDF-HFP), lithium bis(trifluoromethane)sulfonimide (LiTFSI) and PDA@LLZTO.

Benefits of technology

The ionic conductivity and thermal stability of the composite electrolyte membrane are improved, mechanical strength is enhanced, interface compatibility between electrode materials is improved, and electrochemical performance of lithium metal batteries is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

A method for preparing a high-performance polymer / inorganic ceramic composite solid electrolyte, which relates to a method for preparing a composite solid electrolyte. The purpose of the present invention is to solve the problems of low mechanical strength of existing pure inorganic solid electrolytes, interface problems with electrode materials, and low ion conductivity and ion migration number at room temperature. Method: 1. Prepare PDA@LLZTO powder; 2. Prepare a composite solid electrolyte. The high-performance polymer / inorganic ceramic composite solid electrolyte has high ionic conductivity. At a rate of 0.1C, the maximum capacity of the LiFePO4 / PPPL‑10 / Li battery can reach 164.2mAh g ‑1 After 100 cycles, the capacity remains at 157.8 mA hg ‑1 The capacity retention rate is as high as 96.1%. The composite electrolyte membrane provided by the invention has practical significance. The invention can obtain a high-performance polymer / inorganic ceramic composite solid electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a composite solid electrolyte. Background Art

[0002] Lithium-ion batteries have become the third generation of energy storage power sources after nickel-cadmium batteries and nickel-hydrogen batteries due to their high energy density and long cycle life. They are mainly used in energy storage systems such as wind power, hydropower, thermal power and solar power generation, as well as electric vehicles, electric bicycles, military equipment, and aerospace. With the increasing maturity of lithium-ion battery technology, lithium battery pack technology has been widely used in microsatellites, high-orbit satellites, and deep space exploration. However, traditional lithium-ion batteries have always had safety hazards, such as electrolyte leakage and uncontrollable side reactions, as well as abnormal battery temperature rise and diaphragm shrinkage caused by side reactions, which in turn cause battery short circuits, combustion, and explosions. Therefore, it is imperative to develop safe anode and cathode separators with excellent thermal stability and high mechanical strength.

[0003] In recent years, replacing traditional liquid electrolytes and separators with solid electrolytes is regarded as the most effective way to solve the above problems. It can not only solve the safety risks of lithium batteries but also improve the energy density of batteries. Solid electrolytes include oxide solid electrolytes, sulfide solid electrolytes and polymer solid electrolytes. Among them, inorganic solid electrolytes have been proven to have an ion migration number close to 1 and have ultra-high ionic conductivity. However, pure inorganic solid electrolytes will introduce interface problems between electrode materials. Interface incompatibility limits its application in lithium metal batteries. Polymer solid electrolytes, such as poly(ethylene oxide) (PEO), poly(vinylidene fluoride) (PVDF) and poly(vinyl alcohol) (PVA), have high flexibility, good viscoelasticity and easy processing properties. However, the ionic conductivity (σ) and ion migration number (t) are low at room temperature (σ<10 -6 S cm -1 ,t≈0.2-0.4). Summary of the invention

[0004] The purpose of the present invention is to solve the problems of low mechanical strength of existing pure inorganic solid electrolytes, interface problems between electrode materials and low ion conductivity and ion migration number at room temperature, and to provide a method for preparing a high-performance polymer / inorganic ceramic composite solid electrolyte.

[0005] A method for preparing a high-performance polymer / inorganic ceramic composite solid electrolyte is completed by the following steps:

[0006] 1. Preparation of PDA@LLZTO powder:

[0007] ①, dissolving Tris and dopamine hydrochloride in methanol, then adding LLZTO powder, stirring continuously in air atmosphere at room temperature to obtain a reaction product;

[0008] ②, Use methanol to wash the reaction product, and then put it into a vacuum drying oven to dry it to obtain PDA@LLZTO powder;

[0009] 2. Preparation of composite solid electrolyte:

[0010] ①, adding (polyvinylidene fluoride-hexafluoropropylene) copolymer and polyacrylonitrile to N,N-dimethylformamide, and then stirring and reacting at 40°C to 45°C to obtain a mixed solution;

[0011] ②. Add lithium bis(trifluoromethane)sulfonyl imide and PDA@LLZTO powder to the mixed solution, stir the reaction at 40°C to 45°C to obtain a uniformly dispersed solution; pour the uniformly dispersed solution into a polytetrafluoroethylene mold in a glove box, let it stand, and then first use a heating plate to dry it at 45°C to 55°C, and then dry it at 60°C to 80°C to obtain a CSE film containing PDA@LLZTO powder, which is a high-performance polymer / inorganic ceramic composite solid electrolyte.

[0012] Principle of the present invention:

[0013] The present invention first utilizes a mechanical stirring method to 6.4 LqCy 1.4 Ta 0.6 O 12 A layer of polydopamine (PDA) was coated on the surface of (LLZTO) to improve the wettability of LLZTO and reduce the high surface energy of LLZTO for use; secondly, a high-performance polymer / inorganic ceramic composite solid electrolyte (PVDF-HFP / PAN / PDA@LLZTO-LiTFSICPEs), abbreviated as PPPL, was designed by solution casting method, which consists of polyacrylonitrile (PAN), (polyvinylidene fluoride-hexafluoropropylene) copolymer (PVDF-HFP), bis(trifluoromethane) sulfonyl imide lithium (LiTFSI) and PDA@LLZTO; polyvinylidene fluoride (PVDF) has attracted much attention due to its good electrochemical stability and high thermal stability. PVDF-HFP (Poly(vinylidenefluoride-co-hexafluoropropylene)) with the introduction of amorphous phase hexafluoropropylene (HFP) can not only inherit the above advantages of PVDF but also increase the content of fluorine with low crystallinity, thereby enhancing its solubility; PAN (polyacrylonitrile) has excellent mechanical properties, thermal stability, anti-oxidative degradation and high thermal stability at room temperature of about 10 -3 S cm -1However, pure PAN contains polar nitrile (C≡N) groups that react with the Li anode to form a "passivation layer" between the electrode and the electrolyte to increase the interface impedance, and the interaction between the groups prevents the coordination of PAN chains with solvent molecules, reducing the transmission of lithium ions; Fortunately, the blending of these two polymers can greatly alleviate this problem; on this basis, adding the inorganic solid electrolyte PDA@LLZTO can reduce the crystallinity of the polymer and promote the transmission of lithium ions as a lithium ion transmission channel, further improving the ionic conductivity of the blended membrane. Therefore, the lithium metal battery assembled with the composite electrolyte membrane shows ideal electrochemical properties.

[0014] Advantages of the present invention:

[0015] The electrochemical performance and thermal stability of the obtained high-performance polymer / inorganic ceramic composite solid electrolyte were tested. The cycle and constant current charge and discharge tests showed that the high-performance polymer / inorganic ceramic composite solid electrolyte had high ionic conductivity. The maximum capacity of the LiFePO4 / PPPL-10 / Li battery could reach 164.2 mAh g at a rate of 0.1C. -1 After 100 cycles, the capacity remains at 157.8 mA hg -1 The capacity retention rate is as high as 96.1%; it has a high capacity retention rate after 300 cycles at 0.2C (initial capacity 150.7 mAh g -1 , after 300 cycles, the capacity is 111.5 mAhg -1 ); its thermal stability test confirmed that the addition of PAN greatly improved the thermal stability of the composite electrolyte membrane; therefore, the composite electrolyte membrane provided by the present invention has practical significance.

[0016] The invention can obtain a high-performance polymer / inorganic ceramic composite solid electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 (a), (b), (d) and (e) are scanning electron microscope images, and (c) is a transmission electron microscope image. In the figure, (a) is LLZTO powder, (b) and (c) are PDA@LLZTO powders prepared in step 1② of Example 1, (d) is a solid electrolyte prepared in Comparative Example 1 without adding PDA@LLZTO powder, and (e) is PPPL-10 prepared in Example 1;

[0018] Figure 2 EDS spectrum of Zr, Ta, O, La and N of PDA@LLZTO powder prepared in step 1② of Example 1;

[0019] Figure 3: is an XRD spectrum, in which 1 is LLZTO powder, 2 is PDA@LLZTO powder prepared in step 1② of Example 1, and 3 is PPPL-10 prepared in Example 1;

[0020] Figure 4 The cyclic charge-discharge curve of the LiFePO4 / PPPL-10 / Li battery assembled with PPPL-10 prepared in Example 1 as the solid electrolyte at 0.5C, in which 1 is 1 cycle, 2 is 10 cycles, 3 is 50 cycles, 4 is 100 cycles, 5 is 150 cycles, and 6 is 200 cycles;

[0021] Figure 5 This is a test diagram of the cycle performance of a LiFePO4 / PPPL-10 / Li battery assembled with PPPL-10 prepared in Example 1 as a solid electrolyte at 0.1C;

[0022] Figure 6 This is a test diagram of the cycle performance of a LiFePO4 / PPPL-10 / Li battery assembled with PPPL-10 prepared in Example 1 as a solid electrolyte at 0.2C;

[0023] Figure 7 1 is the ionic conductivity of the composite solid electrolyte membrane with different amounts of PDA@LLZTO at different temperatures. In the figure, 1 is the solid electrolyte prepared in Comparative Example 1 without adding PDA@LLZTO powder, 2 is PPPL-10 prepared in Example 1; 3 is PPPL-5 prepared in Example 2, and 4 is PPPL-15 prepared in Example 3;

[0024] Figure 8 The thermal performance diagram of the solid electrolyte membrane at different temperatures, in which row A is PPPL-10 prepared in Example 1, row B is the solid electrolyte prepared in Comparative Example 2 without adding PAN, and RT is room temperature;

[0025] Fig. 9 TEM image of the composite solid electrolyte membrane prepared in Comparative Example 3;

[0026] Fig.10 The cyclic charge-discharge curve of the LiFePO4 / composite solid electrolyte membrane / Li battery assembled with the composite solid electrolyte membrane prepared in Comparative Example 3 at 0.5C, in which 1 is 1 cycle, 2 is 10 cycles, 3 is 50 cycles, 4 is 100 cycles, 5 is 150 cycles, and 6 is 200 cycles;

[0027] Fig.11 1 is the stress-strain curve of the composite electrolyte membrane, in which 1 is the PPPL-10 solid electrolyte prepared in Example 1, and 2 is the composite electrolyte membrane prepared in Comparative Example 4. DETAILED DESCRIPTION

[0028] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all fall within the scope of the present invention.

[0029] Specific implementation method 1: This implementation method is a method for preparing a high-performance polymer / inorganic ceramic composite solid electrolyte, which is specifically completed by the following steps:

[0030] 1. Preparation of PDA@LLZTO powder:

[0031] ①, dissolving Tris and dopamine hydrochloride in methanol, then adding LLZTO powder, stirring continuously in air atmosphere at room temperature to obtain a reaction product;

[0032] ②, Use methanol to wash the reaction product, and then put it into a vacuum drying oven to dry it to obtain PDA@LLZTO powder;

[0033] 2. Preparation of composite solid electrolyte:

[0034] ①, adding (polyvinylidene fluoride-hexafluoropropylene) copolymer and polyacrylonitrile to N,N-dimethylformamide, and then stirring and reacting at 40°C to 45°C to obtain a mixed solution;

[0035] ②. Add lithium bis(trifluoromethane)sulfonyl imide and PDA@LLZTO powder to the mixed solution, stir the reaction at 40°C to 45°C to obtain a uniformly dispersed solution; pour the uniformly dispersed solution into a polytetrafluoroethylene mold in a glove box, let it stand, and then first use a heating plate to dry it at 45°C to 55°C, and then dry it at 60°C to 80°C to obtain a CSE film containing PDA@LLZTO powder, which is a high-performance polymer / inorganic ceramic composite solid electrolyte.

[0036] Specific implementation method 2: The difference between this implementation method and specific implementation method 1 is that the mass ratio of Tris described in step 1① to methanol is (36mg-42mg):30mL; the mass ratio of dopamine hydrochloride described in step 1① to methanol is (60mg-70mg):30mL; the mass ratio of LLZTO powder described in step 1① to methanol is (2.5g-4.5g):30mL. The other steps are the same as those in specific implementation method 1.

[0037] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the stirring speed in step 1① is 300r / min to 500r / min and the stirring time is 12h to 16h. The other steps are the same as those in specific implementation method 1 or 2.

[0038] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: in step 1 ②, methanol is used to wash the reaction product 2 to 5 times; the temperature of the vacuum drying oven in step 1 ② is 55° C. to 60° C. The other steps are the same as those of specific embodiments 1 to 3.

[0039] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the weight average molecular weight Mw of the (polyvinylidene fluoride-hexafluoropropylene) copolymer described in step 2① is 455 000. The other steps are the same as those of specific embodiments 1 to 4.

[0040] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that the weight average molecular weight Mw of the polyacrylonitrile described in step 2① is 150000. The other steps are the same as those of specific embodiments 1 to 5.

[0041] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the mass ratio of the (polyvinylidene fluoride-hexafluoropropylene) copolymer to polyacrylonitrile in step 2① is 9:1. The other steps are the same as those of specific embodiments 1 to 6.

[0042] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that: the mass ratio of the (polyvinylidene fluoride-hexafluoropropylene) copolymer described in step 2① to the volume ratio of N,N-dimethylformamide is 0.9g:10mL; the stirring speed described in step 2① is 500r / min to 600r / min, and the stirring time is 4h to 6h. The other steps are the same as those of specific embodiments 1 to 7.

[0043] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that the ratio of the mass of lithium bis(trifluoromethane)sulfonyl imide described in step 2② to the total mass of (polyvinylidene fluoride-hexafluoropropylene) copolymer and polyacrylonitrile is 1:3; the PDA@LLZTO powder described in step 2② accounts for 5% to 20% of the total mass of (polyvinylidene fluoride-hexafluoropropylene) copolymer, polyacrylonitrile, and lithium bis(trifluoromethane)sulfonyl imide PDA@LLZTO powder. The other steps are the same as specific embodiments 1 to 8.

[0044] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that: the stirring reaction speed in step 2② is 800r / min to 1000r / min, and the stirring reaction time is 10h to 12h; in step 2②, first use a heating plate to dry at 45℃ to 55℃ for 4h to 6h, and then dry at 60℃ to 80℃ for 2h to 4h; the standing time in step 2② is 10min to 30min. The other steps are the same as those in specific embodiments 1 to 8.

[0045] The following examples are used to verify the beneficial effects of the present invention:

[0046] Example 1: A method for preparing a high-performance polymer / inorganic ceramic composite solid electrolyte is specifically completed by the following steps:

[0047] 1. Preparation of PDA@LLZTO powder:

[0048] ①, 36 mg Tris and 60 mg dopamine hydrochloride were dissolved in 30 mL methanol, and then 2.5 g LLZTO powder was added, and the mixture was stirred continuously for 14 h at room temperature in an air atmosphere and at a stirring speed of 400 r / min to obtain a reaction product;

[0049] ②, the reaction product was washed with methanol for 5 times, and then placed in a vacuum drying oven at 60°C for 6 hours to obtain PDA@LLZTO powder;

[0050] 2. Preparation of composite solid electrolyte:

[0051] ①, adding (polyvinylidene fluoride-hexafluoropropylene) copolymer and polyacrylonitrile into 10mL N,N-dimethylformamide, and stirring for 6h at 45°C and a stirring speed of 500r / min to obtain a mixed solution;

[0052] The weight average molecular weight Mw of the (polyvinylidene fluoride-hexafluoropropylene) copolymer described in step 2① is 455,000;

[0053] The weight average molecular weight Mw of the polyacrylonitrile described in step 2① is 150000;

[0054] The mass ratio of the (polyvinylidene fluoride-hexafluoropropylene) copolymer described in step 2① to polyacrylonitrile is 9:1;

[0055] The volume ratio of the (polyvinylidene fluoride-hexafluoropropylene) copolymer described in step 2① to N,N-dimethylformamide is 0.9 g:10 mL;

[0056] ②, add lithium bis(trifluoromethane)sulfonyl imide and PDA@LLZTO powder to the mixed solution, stir the reaction at 45°C and a stirring speed of 800r / min for 12h to obtain a uniformly dispersed solution; pour the uniformly dispersed solution into a polytetrafluoroethylene mold in a glove box, and then let it stand for 30min. After standing, first use a heating plate to dry at 45°C for 6h, and then dry at 60°C for 4h to obtain a CSE film containing PDA@LLZTO powder, which is a high-performance polymer / inorganic ceramic composite solid electrolyte (PPPL-10);

[0057] The ratio of the mass of lithium bis(trifluoromethane)sulfonyl imide described in step 2② to the total mass of (polyvinylidene fluoride-hexafluoropropylene) copolymer and polyacrylonitrile is 1:3;

[0058] The PDA@LLZTO powder described in step 2② accounts for 10% of the total mass of the (polyvinylidene fluoride-hexafluoropropylene) copolymer, polyacrylonitrile, lithium bis(trifluoromethane)sulfonyl imide and PDA@LLZTO powder.

[0059] Example 2: The difference between this example and Example 1 is that the PDA@LLZTO powder described in step 2② accounts for 5% of the total mass of (polyvinylidene fluoride-hexafluoropropylene) copolymer, polyacrylonitrile, lithium bis(trifluoromethane)sulfonyl imide and PDA@LLZTO powder. Step 2② obtains a CSE film containing PDA@LLZTO powder, which is a high-performance polymer / inorganic ceramic composite solid electrolyte (PPPL-5). The other steps and parameters are the same as those in Example 1.

[0060] Example 3: The difference between this example and Example 1 is that the PDA@LLZTO powder described in step 2② accounts for 15% of the total mass of (polyvinylidene fluoride-hexafluoropropylene) copolymer, polyacrylonitrile, lithium bis(trifluoromethane)sulfonyl imide and PDA@LLZTO powder. Step 2② obtains a CSE film containing PDA@LLZTO powder, which is a high-performance polymer / inorganic ceramic composite solid electrolyte (PPPL-15). The other steps and parameters are the same as those in Example 1.

[0061] Comparative Example 1: The solid electrolyte without adding PDA@LLZTO powder was prepared by the following steps:

[0062] 1. Add (polyvinylidene fluoride-hexafluoropropylene) copolymer and polyacrylonitrile into 10 mL of N,N-dimethylformamide, and then stir and react for 6 hours at 45° C. and a stirring speed of 500 r / min to obtain a mixed solution;

[0063] The weight average molecular weight Mw of the (polyvinylidene fluoride-hexafluoropropylene) copolymer described in step 1 is 455000;

[0064] The weight average molecular weight Mw of the polyacrylonitrile described in step 1 is 150000;

[0065] The mass ratio of the (polyvinylidene fluoride-hexafluoropropylene) copolymer described in step 1 to polyacrylonitrile is 9:1;

[0066] The volume ratio of the (polyvinylidene fluoride-hexafluoropropylene) copolymer described in step 1 to N,N-dimethylformamide is 0.9 g:10 mL;

[0067] 2. Add lithium bis(trifluoromethane)sulfonyl imide to the mixed solution, stir the reaction at 45°C and a stirring speed of 800 r / min for 12 hours to obtain a uniformly dispersed solution; pour the uniformly dispersed solution into a polytetrafluoroethylene mold in a glove box, and then let it stand for 30 minutes. After standing, first use a heating plate to dry it at 45°C for 6 hours, and then dry it at 60°C for 4 hours to obtain a solid electrolyte without adding PDA@LLZTO powder;

[0068] The ratio of the mass of lithium bis(trifluoromethane)sulfonyl imide described in step 2 to the total mass of the (polyvinylidene fluoride-hexafluoropropylene) copolymer and polyacrylonitrile is 1:3.

[0069] Comparative Example 2: The preparation of the solid electrolyte without adding PAN is completed according to the following steps:

[0070] 1. Preparation of PDA@LLZTO powder:

[0071] ①, 36 mg Tris and 60 mg dopamine hydrochloride were dissolved in 30 mL methanol, and then 2.5 g LLZTO powder was added, and the mixture was stirred continuously for 14 h at room temperature in an air atmosphere and at a stirring speed of 400 r / min to obtain a reaction product;

[0072] ②, the reaction product was washed with methanol for 5 times, and then placed in a vacuum drying oven at 60°C for 6 hours to obtain PDA@LLZTO powder;

[0073] 2. Preparation of composite solid electrolyte:

[0074] ①, add (polyvinylidene fluoride-hexafluoropropylene) copolymer into 10mL N,N-dimethylformamide, and then stir and react for 6h at 45°C and a stirring speed of 500r / min to obtain a mixed solution;

[0075] The weight average molecular weight Mw of the (polyvinylidene fluoride-hexafluoropropylene) copolymer described in step 2① is 455,000;

[0076] The volume ratio of the (polyvinylidene fluoride-hexafluoropropylene) copolymer described in step 2① to N,N-dimethylformamide is 1 g:10 mL;

[0077] ②, add lithium bis(trifluoromethane)sulfonyl imide and PDA@LLZTO powder to the mixed solution, stir the reaction at 45°C and a stirring speed of 800r / min for 12h to obtain a uniformly dispersed solution; pour the uniformly dispersed solution into a polytetrafluoroethylene mold in a glove box, and then let it stand for 30min. After standing, first use a heating plate to dry at 45°C for 6h, and then dry at 60°C for 4h to obtain a CSE film containing PDA@LLZTO powder, which is a high-performance polymer / inorganic ceramic composite solid electrolyte (PPPL-10);

[0078] The mass ratio of the lithium bis(trifluoromethane)sulfonyl imide described in step 2② to the (polyvinylidene fluoride-hexafluoropropylene) copolymer is 1:3;

[0079] The PDA@LLZTO powder described in step 2② accounts for 10% of the total mass of the (polyvinylidene fluoride-hexafluoropropylene) copolymer, lithium bis(trifluoromethane)sulfonyl imide and PDA@LLZTO powder.

[0080] Figure 1 (a), (b), (d) and (e) are scanning electron microscope images, and (c) is a transmission electron microscope image. In the figure, (a) is LLZTO powder, (b) and (c) are PDA@LLZTO powders prepared in step 1② of Example 1, (d) is a solid electrolyte prepared in Comparative Example 1 without adding PDA@LLZTO powder, and (e) is PPPL-10 prepared in Example 1;

[0081] from Figure 1 (a) shows that the surface roughness particle size is about 2-5 μm. Figure 1 (b) and (c) show that the surface of LLZTO coated with PDA is smooth and glossy. Figure 1 (d) and (e) the filling of PDA@LLZTO can be clearly observed.

[0082] Figure 2 EDS spectrum of Zr, Ta, O, La and N of PDA@LLZTO powder prepared in step 1② of Example 1;

[0083] Depend on Figure 2 It can be seen that N element, which is not present in LLZTO, appears after PDA coating, proving the successful coating of PDA.

[0084] Figure 3: is an XRD spectrum, in which 1 is LLZTO powder, 2 is PDA@LLZTO powder prepared in step 1② of Example 1, and 3 is PPPL-10 prepared in Example 1;

[0085] from Figure 3 It can be seen that all diffraction peaks match those of cubic phase LLZTO (JCPDS 80-0457).

[0086] The assembly method of LiFePO4 / PPPL-10 / Li battery is completed in the following steps:

[0087] The LiFePO4 / PPPL-10 / Li battery comprises a positive electrode shell, a positive electrode material, an electrolyte, a negative electrode material, a gasket, a spring and a negative electrode shell.

[0088] Preparation process of positive electrode: LiFePO4 (LFP), super P and PVDF binder are weighed and bottled at a mass ratio of 8:1:1 and soaked with an appropriate amount of N-methylpyrrolidone (the mass of LFP is 0.4g). Stir at a speed of 600r / min until it becomes viscous, and apply the slurry on a clean aluminum foil with a four-sided preparation device, and then put the aluminum foil with slurry into an oven at 80-90℃ to dry; before use, punch the positive electrode material into a disc with a diameter of 12mm.

[0089] The PPPL-10 composite electrolyte prepared in Example 1 was punched into 18 mm discs before use.

[0090] The negative electrode is a lithium sheet with a diameter of 16mm and a thickness of 0.6mm.

[0091] Assembly method: Use plastic tweezers to pick up the prepared positive electrode and place it in the center of the positive electrode shell, and use a pipette to take 2μL of LiPF6 electrolyte and drop it on the surface of the positive electrode; then, place the electrolyte sheet on the positive electrode sheet (because it has the same diameter as the positive electrode shell, there is no need to specially calibrate the center position), and use a pipette to take 2μL of LiPF6 electrolyte and drop it on the surface of the electrolyte; then place the lithium sheet in the center of the electrolyte, and stack the gasket and shrapnel on the lithium sheet in turn; finally, cover the negative electrode shell and seal it with a battery packaging machine.

[0092] Figure 4 The cyclic charge-discharge curve of the LiFePO4 / PPPL-10 / Li battery assembled with PPPL-10 prepared in Example 1 as the solid electrolyte at 0.5C, in which 1 is 1 cycle, 2 is 10 cycles, 3 is 50 cycles, 4 is 100 cycles, 5 is 150 cycles, and 6 is 200 cycles;

[0093] from Figure 4It can be seen that the charge and discharge curve platform of the battery is relatively flat. The discharge capacity of the battery after the 1st, 10th, 50th, 100th, 150th and 200th cycles is 141.5, 137.4, 131.5, 127.8, 123.4 and 119.3 mAh g -1 .

[0094] Figure 5 This is a test diagram of the cycle performance of a LiFePO4 / PPPL-10 / Li battery assembled with PPPL-10 prepared in Example 1 as a solid electrolyte at 0.1C;

[0095] Figure 5 The results show that after 2 cycles of activation at 0.1C, the maximum capacity of the battery reaches 164.2 mAh g -1 , after 100 cycles, it can still reach 157.8mAh g -1 , the capacity retention rate is 96.1%.

[0096] Figure 6 This is a test diagram of the cycle performance of a LiFePO4 / PPPL-10 / Li battery assembled with PPPL-10 prepared in Example 1 as a solid electrolyte at 0.2C;

[0097] from Figure 6 It can be seen that at 0.2C, the capacity retention rate after 300 cycles is about 74.0%, and the Coulomb efficiency is close to 100% (the first cycle, 150.7 mAh g -1 ; 300 cycles, 111.5mAhg -1 ).

[0098] In contrast, the maximum capacities of the LiFePO4 / PPPL-5 / Li battery at 0.1, 0.2, and 0.5C are 153.18, 143.43, and 123.13 mAhg, respectively. -1 The maximum capacities of LiFePO4 / PPPL-15 / Li batteries at 0.1, 0.2 and 0.5C are 157.08, 134.18 and 129.50 mAh g, respectively. -1 This proves that the PPPL-10 solid electrolyte prepared by the present invention has better performance.

[0099] Figure 7 1 is the ionic conductivity of the composite solid electrolyte membrane with different amounts of PDA@LLZTO at different temperatures. In the figure, 1 is the solid electrolyte prepared in Comparative Example 1 without adding PDA@LLZTO powder, 2 is PPPL-10 prepared in Example 1; 3 is PPPL-5 prepared in Example 2, and 4 is PPPL-15 prepared in Example 3;

[0100] from Figure 7It can be seen that the composite solid electrolyte prepared by the present invention has the lowest activation energy of 0.13176 eV and the highest ionic conductivity of about 0.4×10 -3 S cm -1 .

[0101] Figure 8 Graphs showing the thermal performance of solid electrolyte membranes at different temperatures. In the graph, row A is PPPL-10 prepared in Example 1, and row B is solid electrolyte prepared in Comparative Example 2 without adding PAN. RT is room temperature.

[0102] from Figure 8 It can be seen that the composite membrane without PAN has multiple bubbles on its surface at 180℃ for 2h, while the electrolyte membrane with PAN has a flat surface and no deformation. Even at 350℃, it is only carbonized without burning or deformation. Therefore, the addition of PAN greatly improves the thermal stability of the composite membrane.

[0103] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that in step 1①, Tris and dopamine hydrochloride are dissolved in methanol, and then LLZTO powder is added, and the mixture is continuously stirred at 55° C. in an air atmosphere to obtain a reaction product. The other steps and parameters are the same as those in Example 1.

[0104] Fig. 9 TEM image of the composite solid electrolyte membrane prepared in Comparative Example 3;

[0105] from Fig. 9 It can be seen that dopamine will self-polymerize into polydopamine at high temperature, and the reaction speed is very fast, thus affecting the coating effect.

[0106] Fig.10 The cyclic charge-discharge curve of the LiFePO4 / composite solid electrolyte membrane / Li battery assembled with the composite solid electrolyte membrane prepared in Comparative Example 3 at 0.5C, in which 1 is 1 cycle, 2 is 10 cycles, 3 is 50 cycles, 4 is 100 cycles, 5 is 150 cycles, and 6 is 200 cycles;

[0107] from Fig.10 It can be seen that compared with the LiFePO4 / PPPL-10 / Li battery assembled with PPPL-10 prepared in Example 1 as the solid electrolyte, the charge and discharge curve platform of the LiFePO4 / composite solid electrolyte membrane / Li battery assembled with the composite solid electrolyte membrane prepared in Comparative Example 3 is not flat, and the discharge capacity of the battery after the 1st, 10th, 50th, 100th, 150th, and 200th cycles is 141.35, 143.52, 141.25, 124.21, 109.47, and 84.15 mAh g -1It can be seen that the capacity of the battery assembled with the composite solid electrolyte membrane prepared in Comparative Example 3 is greatly reduced after 100 or even 200 cycles, indicating that the uniformity of polydopamine coating has a significant effect on the capacity of the battery.

[0108] Comparative Example 4: The difference between Comparative Example 3 and Example 1 is that the mass ratio of the (polyvinylidene fluoride-hexafluoropropylene) copolymer described in step 2① to polyacrylonitrile is 6:4; the volume ratio of the (polyvinylidene fluoride-hexafluoropropylene) copolymer described in step 2① to N,N-dimethylformamide is 0.6g:10mL. The other steps and parameters are the same as those in Example 1.

[0109] Fig.11 1 is the stress-strain curve of the composite electrolyte membrane, in which 1 is the PPPL-10 solid electrolyte prepared in Example 1, and 2 is the composite electrolyte membrane prepared in Comparative Example 4;

[0110] Good mechanical properties are also one of the important characteristics of solid electrolytes; Fig.11 is the stress-strain curve of the composite electrolyte, and it can be seen that the tensile strength of the composite electrolyte membrane prepared in Comparative Example 4 is 3.5 MPa, while the tensile strength of the PPPL-10 solid electrolyte prepared in Example 1 is as high as 6.92 MPa. It can be proved that when the content of PAN becomes higher, the mechanical properties of the composite electrolyte membrane decrease.

Claims

1. A method for preparing a high-performance polymer / inorganic ceramic composite solid electrolyte, characterized in that The preparation method of the composite solid electrolyte is specifically completed according to the following steps:

1. Preparation of PDA@LLZTO powder: ①, dissolving Tris and dopamine hydrochloride in methanol, then adding LLZTO powder, stirring continuously in air atmosphere at room temperature to obtain a reaction product; ②, Use methanol to wash the reaction product, and then put it into a vacuum drying oven to dry it to obtain PDA@LLZTO powder; 2. Preparation of composite solid electrolyte: ①, adding (polyvinylidene fluoride-hexafluoropropylene) copolymer and polyacrylonitrile to N,N-dimethylformamide, and then stirring and reacting at 40°C to 45°C to obtain a mixed solution; ②. Add lithium bis(trifluoromethane)sulfonyl imide and PDA@LLZTO powder to the mixed solution, stir the reaction at 40°C to 45°C to obtain a uniformly dispersed solution; pour the uniformly dispersed solution into a polytetrafluoroethylene mold in a glove box, let it stand, and then first use a heating plate to dry it at 45°C to 55°C, and then dry it at 60°C to 80°C to obtain a CSE film containing PDA@LLZTO powder, which is a high-performance polymer / inorganic ceramic composite solid electrolyte.

2. The method for preparing a high-performance polymer / inorganic ceramic composite solid electrolyte according to claim 1, characterized in that The mass ratio of Tris described in step 1① to the volume ratio of methanol is (36mg~42mg):30mL; the mass ratio of dopamine hydrochloride described in step 1① to the volume ratio of methanol is (60mg~70mg):30mL; the mass ratio of LLZTO powder described in step 1① to the volume ratio of methanol is (2.5g~4.5g):30mL.

3. The method for preparing a high-performance polymer / inorganic ceramic composite solid electrolyte according to claim 1, characterized in that The stirring speed described in step 1① is 300r / min~500r / min, and the stirring time is 12h~16h.

4. The method for preparing a high-performance polymer / inorganic ceramic composite solid electrolyte according to claim 1, characterized in that In step 1 ②, methanol is used to wash the reaction product 2 to 5 times; the temperature of the vacuum drying oven described in step 1 ② is 55° C. to 60° C.

5. The method for preparing a high-performance polymer / inorganic ceramic composite solid electrolyte according to claim 1, characterized in that The weight average molecular weight Mw of the (polyvinylidene fluoride-hexafluoropropylene) copolymer described in step 2① is 455,000.

6. The method for preparing a high-performance polymer / inorganic ceramic composite solid electrolyte according to claim 1, characterized in that The weight average molecular weight Mw of the polyacrylonitrile described in step 2① is 150,000.

7. The method for preparing a high-performance polymer / inorganic ceramic composite solid electrolyte according to claim 1, characterized in that The mass ratio of the (polyvinylidene fluoride-hexafluoropropylene) copolymer described in step 2① to polyacrylonitrile is 9:

1.

8. The method for preparing a high-performance polymer / inorganic ceramic composite solid electrolyte according to claim 1, characterized in that The volume ratio of the (polyvinylidene fluoride-hexafluoropropylene) copolymer described in step 2① to N,N-dimethylformamide is 0.9g:10mL; the stirring speed described in step 2① is 500r / min~600r / min, and the stirring time is 4h~6h.

9. The method for preparing a high-performance polymer / inorganic ceramic composite solid electrolyte according to claim 1, characterized in that The ratio of the mass of lithium bis(trifluoromethane)sulfonyl imide described in step 2② to the total mass of (polyvinylidene fluoride-hexafluoropropylene) copolymer and polyacrylonitrile is 1:3; the PDA@LLZTO powder described in step 2② accounts for 5% to 20% of the total mass of (polyvinylidene fluoride-hexafluoropropylene) copolymer, polyacrylonitrile, lithium bis(trifluoromethane)sulfonyl imide and PDA@LLZTO powder.

10. The method for preparing a high-performance polymer / inorganic ceramic composite solid electrolyte according to claim 1, characterized in that The stirring reaction speed described in step 2② is 800r / min~1000r / min, and the stirring reaction time is 10h~12h; in step 2②, first use a heating plate to dry at 45℃~55℃ for 4h~6h, and then dry at 60℃~80℃ for 2h~4h; the standing time described in step 2② is 10min~30min.

Citation Information

Patent Citations

  • Composite solid polymer electrolyte film and preparation method and application thereof

    CN109546207A

  • Lithium ion conductive composite material for all solid-state lithium battery, and solid polymer electrolyte and all solid-state lithium battery including the same

    CN112490498A